Study of Babesia microti acquisition by ticks - Šnebergerová, Pavla (Jihočeská univerzita, 2019)
Acquisition of the apicomplexan parasite Babesia microti by the tick host has not been intensively investigated so far. To address this circumstance, AMA-1 (Apical membrane antigen-1) known to participate in host cell invasion, and sexual stage-specific protein CCp2 were selected as potential markers of B. microti developmental stages inside the tick host. In line with previous research, AMA-1 has been validated by indirect immunofluorescence as a specific antigen of B. microti invasive stages in vertebrate host blood. In addition, the immunogenic potential of this protein was confirmed. Despite the ama-1 gene expression was examined in tick organs, AMA-1 protein was not detected in parasite stages - presumably kinetes - observed in epithelial cells of the tick gut wall. Therefore, AMA-1 protein does not appear to be a suitable universal marker of B. microti invasive stages in the tick. The ccp2 gene expression was confirmed also in the tick tissues and indicates the presence of the sexual stages in the gut lumen. Yet, the specificity of CCp2 protein as a marker for B. microti sexual stages needs to be further investigated.
Study of Babesia microti acquisition by ticks